Ethnobotany Traditional Medicinal Plants by People in Rangkang Village, Kraksaan Sub District, Probolinggo Regency - Fatmawati, Prita Paramitha; Batoro, Jati; Yanuwiadi, Bagyo (Jurnal Pembangunan dan Alam Lestari, 2023)
The purposes of this collaborative research are to reveal the plant species used in traditional medicine, to reveal diseases that can be prevented and treated with medicinal plants, to reveal how to process medicinal plants into traditional medicines, and to analyze the efforts to preserve medicinal plants in Rangkang Village. The methods used are observation, interviews, documentation, and data analysis using Species Use Value (UVs), Family Use Value (FUVs), and SWOT analysis. The results showed 33 species of medicinal plants used by the people of Rangkang Village. Some essential or priority plants for the people of Rangkang Village are betel (Piper betle), papaya (Carica papaya), lime (Citrus aurantifolia), pomegranate (Punica granatum), temu ireng (Curcuma aeroginosa), turmeric (Curcuma longa), noni (Morinda citrifolia), galangal (Alpinia galangal), guava (Psidium guajava), soursop (Annona muricata) and white turmeric (Curcuma mango). There are 27 medicinal plant families with different FUVs values. The strategy for conserving the diversity of medicinal plants in Rangkang village is by maintaining and preserving the wealth of natural resources owned, forming a farmer community to preserve medicinal plants, and collaborating with the government or Non-Government Organisations counseling the local community.  Keywords: ethnobotany, rangkang village, conservation strategy, medicinal plant